Sistem Informasi Online Public Access Catalog (OPAC) Dan Digitalisasi Koleksi Pustaka Berbasis Web Di Perpustakaan Jebres - Evi Febrianti; Chairullah Naury; Mursid Dwi Hastomo (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The library collection is the most important part of Jebres Library which has been owned and available from the beginning of the opening, over time the problems experienced by Jebres library in the utilization of library collections are the damage to printed collections made from paper and the age of printed collections that are getting older making the quality of paper-based collections vulnerable to damage so that preservation measures are needed so that library collections can still be used by users. Preservation of library collections is carried out to save the content of information in library collections, one of the efforts to preserve library collections is by digitizing. Digitization is the process of converting media from print to digital or electronic form. In this case the author conducts research that aims to create an Online Public Access Catalog (OPAC) Information System for Web-Based Library Collection Digitization at Jebres Library, a catalog system to display library collections that have been digitized. In this study, the authors used the SDLC (System Development Life Cycle) method in the system development process and the PHP programming language and used the MySQL database. The system that the author designed is expected to facilitate users in utilizing library collections and assist librarians in carrying out the process of preserving library collections and monitoring library collections that have been digitized.